Derivational Affixes Found on Instagram Post @poemsporn_ - Miftah Karisma Wulan Andadari; Putu Devi Maharani; I.B. Gde Nova Winarta (TEKNOSASTIK, 2022)
The study is focused on to find out the types of derivational affixes, the function, and the general meaning of each word found in the Instagram Post @poemsporn_. This study is used the theory propose by Brinton (2010) about the types and function of derivational affixes and Katamba (1994) about the general meaning of derivational affixes. The writer used the observation procedure method which used before analyzing the data. Then, the writer used the descriptive-qualitative method. In addition, for presented the data, the writer used an informal method to present the data. This study found there are 34 words indicated as derivational affixes. The prefixes are 5 words. They consist of the prefix (Im-), (a-), (In-), and (Un-). However, there are 29 words that indicated as derivational affixes by adding suffixes (-ing), (-ly), (-ness), (-or), (-ful), (-less), (-ion), (-ance). In addition, the function of words found is indicated as class changing consist of 33 words, while class maintaining is 2 words. The class changing functions are from verb to noun, adjective to noun, noun to adjective, and adjective to adverb. Meanwhile, the class maintaining function is from adjective to adjective.